2000
DOI: 10.1080/13546800050199711
|View full text |Cite
|
Sign up to set email alerts
|

Automatic without autonomic responses to familiar faces: Differential components of covert face recognition in a case of Capgras delusion

Abstract: Introduction. This study was designed to elucidate the relationship between different types of covert face recognition. Some patients with prosopagnosia (i.e., the profound inability to recognise previously familiar faces) nonetheless evince autonomic face recognition (elevated skin-conductance levels to familiar faces) or behavioural indices of covert recognition (i.e., priming; interference effects; matching effects; face-name learning). One prosopagnosic patient revealed both autonomic and behavioural cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 40 publications
0
20
1
1
Order By: Relevance
“…According to this analysis, the Capgras patient recognizes a face as familiar at an intellectual level, but fails to experience the feeling of recognition that normally occurs whenever we encounter someone well known to us. In a test of this hypothesis, Ellis, Lewis, Moselhy, and Young (2000) were able to show that Capgras patients did not exhibit the autonomic response that is normally elicited when viewing a familiar face.…”
Section: Perceptual Theoriesmentioning
confidence: 92%
“…According to this analysis, the Capgras patient recognizes a face as familiar at an intellectual level, but fails to experience the feeling of recognition that normally occurs whenever we encounter someone well known to us. In a test of this hypothesis, Ellis, Lewis, Moselhy, and Young (2000) were able to show that Capgras patients did not exhibit the autonomic response that is normally elicited when viewing a familiar face.…”
Section: Perceptual Theoriesmentioning
confidence: 92%
“…Following the procedure detailed in Ellis et al (2000), each face was presented for 2 seconds, with an interval of 20 seconds between stimuli. The first five faces were unfamiliar practice faces and were not analysed.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, they should show no differential responses for familiar compared with unfamiliar faces. This prediction has been tested by Ellis, Lewis, Moselhy, and Young (2000), Ellis, Young, Quayle, and de Pauw (1997b), and Hirstein and Ramachandran (1997). All these studies found that patients with Capgras delusion produced no differential SCRs to familiar and unfamiliar faces.…”
mentioning
confidence: 87%
“…To answer this question Ellis et al (2000) tested B.P., a 69-year-old woman with Capgras delusion, together with six non-psychiatric controls. Each was given a standard familiar/unfamiliar face SCR test; a self-priming task (names to be classified for familiarity preceded by same face or another's face); and an interference test (incidental faces present while names were classified by occupation).…”
Section: Unconscious Recognitionmentioning
confidence: 99%